Real-time data and fiscal policy analysis: a survey of the literature - Jacopo Cimadomo (European Central Bank (ECB), 2011)
This paper surveys the empirical research on fiscal policy analysis based on real-time data. This literature can be broadly divided in three groups that focus on: (1) the statistical properties of revisions in fiscal data; (2) the political and institutional determinants of projection errors by governments and (3) the reaction of fiscal policies to the business cycle. It emerges that, first, fiscal data revisions are large and initial releases are biased estimates of final values. Second, the presence of strong fiscal rules and institutions leads to relatively more accurate releases of fiscal data and small deviations of fiscal outcomes from government plans. Third, the cyclical stance of fiscal policies is estimated to be more `counter-cyclical' when real-time data are used instead of ex-post data. Finally, more work is needed for the development of real-time datasets for fiscal policy analysis. In particular, a comprehensive real-time dataset including fiscal variables for industrialized (and possibly developing) countries, published and maintained by central banks or other institutions, is still missing.
Keywords: E62; H60; H68; 330; cyclical sensitivity; data revisions; Fiscal Policy; real-time data